Cognitive Theory in Action: A Discourse Analysis to a Youtube Video about Teaching - Savira, Siti Ina (Jurnal Psikologi Teori dan Terapan, 2011)
Video offers a richer source of data and has been proven to be useful as a primary source of research. A video from Youtube website was used as a primary source for analysis in this paper. This paper is applying a discourse analysis as suggested by Fairclough (2003) about the discourse as a way of representing; how the discourse was used to express and imply the social relation and action, and the belief committed by the user of the discourse. The analysis was aimed to identify teacherâs idea of good teaching by comparing it to relevant theories. The analysis found that cognitive-related terms were consistently appearing in the teacherâs discourses; therefore, cognitive theories were used to elaborate a deeper meaning of the discourses. It was concluded that good teaching for the teacher was to focus on studentsâ cognitive higher development.